2016
DOI: 10.1155/2016/4203160
|View full text |Cite
|
Sign up to set email alerts
|

Multiport Combined Endoscopic Approach to Nonembolized Juvenile Nasopharyngeal Angiofibroma with Parapharyngeal Extension: An Emerging Concept

Abstract: Background. Surgical approaches to the parapharyngeal space (PPS) are challenging by virtue of deep location and neurovascular content. Juvenile Nasopharyngeal Angiofibroma (JNA) is a formidable hypervascular tumor that involves multiple compartments with increase in size. In tumors with extension to parapharyngeal space, the endonasal approach was observed to be inadequate. Combined Endoscopic Endonasal Approaches and Endoscopic Transoral Surgery (EEA-ETOS) approach has provided a customized alternative of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Reviewing the literature concerning the multiportal combined endonasal and transorbital approach to the skull base, we found a total of 24 patients (16 women, 8 men; mean age 32.5 years) with skull base neoplasms who underwent a combined endoscopic endonasal and transorbital approach. [20][21][22]37,50,51 The literature review revealed that in the majority of cases the diagnosis was a meningioma (15/24 cases, 63%), followed by chondrosarcoma (2/24 cases, 8%). Interestingly, in 29% of the cases, such a combined approach was used to treat a recurrent neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the literature concerning the multiportal combined endonasal and transorbital approach to the skull base, we found a total of 24 patients (16 women, 8 men; mean age 32.5 years) with skull base neoplasms who underwent a combined endoscopic endonasal and transorbital approach. [20][21][22]37,50,51 The literature review revealed that in the majority of cases the diagnosis was a meningioma (15/24 cases, 63%), followed by chondrosarcoma (2/24 cases, 8%). Interestingly, in 29% of the cases, such a combined approach was used to treat a recurrent neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…6,[38][39][40][41][42] On the other hand, involvement of the entire parotid gland, lateral skull base, or neck lymph nodes should lead to adoption of a lateral approach. In particular, when the lesion involves the sinonasal tract, nasopharynx, median/paramedian skull base, pterygopalatine fossa, masticatory space, nasopharynx, oropharynx, and/or oral cavity, a transnasal, TO, or combined transnasal-TO approach should always be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, when the lesion involves the sinonasal tract, nasopharynx, median/paramedian skull base, pterygopalatine fossa, masticatory space, nasopharynx, oropharynx, and/or oral cavity, a transnasal, TO, or combined transnasal-TO approach should always be considered. 6,[38][39][40][41][42] On the other hand, involvement of the entire parotid gland, lateral skull base, or neck lymph nodes should lead to adoption of a lateral approach. 5,13,43 To provide a complete spectrum of the anatomic routes to the PPS, the present preclinical study intentionally also included invasive approaches requiring mandibulotomy or mandibulectomy (TOMan, TCMan, ITFA-D, ITFA-C), which are rarely adopted or are even considered obsolete.…”
Section: Discussionmentioning
confidence: 99%
“…Its vascularity, propensity to grow intracranially through various fissures and foramina in the base skull and its ability to burrow into the marrow spaces in diploic bone without destroying the surrounding compact bone makes it a challenge to operate upon successfully. There have been many approaches described for excising these tumors -the traditional open approaches, the endoscopic approach [1], the combined or endoscopic assisted approach [2,3], the Push-Pull approach [4] the endoscopic Modified Denker's approach [5] and more recently the multiport approaches through both the nasal and oral cavities [6,7]. We propose a technique whereby large, lateral extensions of the tumors can be accessed and removed without violating the anterior facial skeleton, thereby preventing facial deformity in the future.…”
Section: Introductionmentioning
confidence: 99%